2009
DOI: 10.1038/ng.275
|View full text |Cite|
|
Sign up to set email alerts
|

Ulcerative colitis–risk loci on chromosomes 1p36 and 12q15 found by genome-wide association study

Abstract: Ulcerative colitis is a chronic inflammatory disease of the colon that presents as diarrhea and gastrointestinal bleeding. We performed a genome-wide association study using DNA samples from 1,052 individuals with ulcerative colitis and pre-existing data from 2,571 controls, all of European ancestry. In an analysis that controlled for gender and population structure, ulcerative colitis loci attaining genome-wide significance and subsequent replication in two independent populations were identified on chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
280
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(291 citation statements)
references
References 28 publications
(49 reference statements)
8
280
1
2
Order By: Relevance
“…5,6 Of the two types of IBD, the genetic contribution to disease risk has been documented more extensively and clearly for CD [7][8][9][10][11][12][13][14][15][16][17] than for UC. [18][19][20][21] So far, linkage and genome-wide association studies have identified more than 30 CD-susceptibility loci in Caucasian populations. 22 Of those, NOD2, ATG16L1 and IRGM were CD specific, whereas genes involved in Th17 differentiation, including IL23R, IL12B, JAK2, STAT3 and TNFSF15 were shared between UC and CD in Caucasians.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Of the two types of IBD, the genetic contribution to disease risk has been documented more extensively and clearly for CD [7][8][9][10][11][12][13][14][15][16][17] than for UC. [18][19][20][21] So far, linkage and genome-wide association studies have identified more than 30 CD-susceptibility loci in Caucasian populations. 22 Of those, NOD2, ATG16L1 and IRGM were CD specific, whereas genes involved in Th17 differentiation, including IL23R, IL12B, JAK2, STAT3 and TNFSF15 were shared between UC and CD in Caucasians.…”
Section: Introductionmentioning
confidence: 99%
“…NOD2, the first gene linked with increased susceptibility to CD, has later been shown to be associated with ileal disease, early age of onset, stricturing, and/or penetrating phenotype and increased need for surgery [5,9,10,[38][39][40][41][42][43][44][45][46][47][48][49]. Among the UC susceptibility genes, HLA DRB1*0103 and the multidrug resistance gene 1 (MDR1/ABCB1) were also identified as being associated with extensive and severe disease [17,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Among the UC susceptibility genes, HLA DRB1*0103 and the multidrug resistance gene 1 (MDR1/ABCB1) also contribute to clinical phenotype and natural history, being associated with extensive and severe disease [17,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. In CD, NOD2 gene mutations have repeatedly been shown to be associated with ileal disease, early age of onset, stricturing, and/or penetrating phenotype and increased need for surgery [5,9,10,[38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Novel susceptibility loci have been identified for UC in Japanese population 109 but they were not detected in the other three GWAS conducted in Europeans. [110][111][112] Attempts to dissect the genetic basis of early-onset or pediatric-onset IBD have also yielded some success, where several previously unreported regions for IBD have been identified. [113][114] In addition, the GWAS also found associations of many loci previously implicated for adult-onset CD and UC with early-onset IBD, thus for the first time suggesting a close relationship in the patho-physiology between early-and adult-onset IBD.…”
Section: The Recent 2 Years: 2008 and 2009mentioning
confidence: 99%